Elucidating the subunit composition of tRNA-guanine transglycosylase in Trypanosoma brucei - Běhálková, Veronika (Jihočeská univerzita, 2017)
The aim of this thesis was to elucidate the relationship and/or interaction between two tRNA-guanine transglycosylase paralogs (putative subunits of the TGT enzyme) identified in Trypanosoma brucei. The overexpression of these proteins was tested in a rescue experiment in a Schizosaccharomyces pombe experimental system.
Elucidating the subunit composition of tRNA-guanine transglycosylase in Trypanosoma brucei
Keywords: tRNA-guanine transglycosylase; TGT; queuosine; Q; queuine; Trypanosoma brucei; Schizosaccharomyces pombe; tRNA-guanine transglycosylase; TGT; queuosine; Q; queuine; Trypanosoma brucei; Schizosaccharomyces pombe